Patulin disrupts SLC7A11-cystine-cysteine-GSH antioxidant system and promotes renal cell ferroptosis both in vitro and in vivo. (August 2022) - Chen, Hui; Cao, Lixing; Han, Kai; Zhang, Han; Cui, Jinling; Ma, Xuan; Zhao, Shuang; Zhao, Chong; Yin, Shutao; Fan, Lihong; Hu, Hongbo
Abstract: Patulin (PAT) is a common food-borne mycotoxin with diverse toxic effects including nephrotoxicity. The induction of oxidative stress is suggested to be a key mechanism contributed to toxicities of PAT. Reduced glutathione (GSH), a sulfhydryl-containing tripeptide, is a key reason for PAT-mediated oxidative stress. Cystine/glutamate antiporter (system xc − )-mediated cystine uptake plays a critical role in maintaining redox balance via promoting GSH biosynthesis. In this study, we addressed if GSH reduction by PAT was associated with inhibition of system xc − -mediated GSH biosynthesis. Results showed that PAT significantly decreased activity of SLC7A11, a core subunit of system xc −, through activating AMPK-mediated formation of beclin1-SLC7A11 complex. Furthermore, PAT promoted ferroptosis induced by a known ferroptosis inducer RSL3 in normal renal cells, and exacerbated folic acid-induced nephrotoxicity in a mouse model of acute kidney injury. The findings of the present study provide new insights into PAT-induced kidney toxicity, and implicate that patients with ferroptosis-associated diseases maybe more susceptible to PAT. Graphical abstract: Image 1